2018
DOI: 10.1016/j.celrep.2018.02.049
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt Cooperates with Oncogenic Notch by Inducing Nitric Oxide-Dependent Inflammation

Abstract: The PI3K/Akt signaling pathway, Notch, and other oncogenes cooperate in the induction of aggressive cancers. Elucidating how the PI3K/Akt pathway facilitates tumorigenesis by other oncogenes may offer opportunities to develop drugs with fewer side effects than those currently available. Here, using an unbiased in vivo chemical genetic screen in Drosophila, we identified compounds that inhibit the activity of proinflammatory enzymes nitric oxide synthase (NOS) and lipoxygenase (LOX) as selective suppressors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 63 publications
0
49
0
1
Order By: Relevance
“…For examples, Guo et al reported that Notch2 negatively regulates cell invasion by inhibiting the PI3K-AKT signaling pathway in gastric cancer [24], and Villegas et al found that PI3K-AKT cooperates with oncogenic Notch by inducing nitric oxide-dependent inflammation [25]. However, few studies have reported the interactions between these pathways in chondrocytes and OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, Guo et al reported that Notch2 negatively regulates cell invasion by inhibiting the PI3K-AKT signaling pathway in gastric cancer [24], and Villegas et al found that PI3K-AKT cooperates with oncogenic Notch by inducing nitric oxide-dependent inflammation [25]. However, few studies have reported the interactions between these pathways in chondrocytes and OA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…p-value ≤ 0.01) among the 24 male-specific eGenes. PI3K-AKT is known to co-operate with Notch by triggering inflammation and immunosuppression [56]. Concurrent activation of Notch and PI3K/AKT pathways can trigger tumorigenesis and is prevalent in aggressive cancers [57][58][59][60].…”
Section: Sex-specific Germline Genetic Effects On Tumor Gene Expressimentioning
confidence: 99%
“…p-value ≤ 0.01) among the 24 male-specific eGenes. PI3K-AKT is known to co-operate with Notch by triggering inflammation and immunosuppression [56]. Concurrent activation of Notch and PI3K/AKT pathways can trigger tumorigenesis and is prevalent in aggressive cancers [57][58][59][60].…”
Section: Sex-specific Germline Genetic Effects On Tumor Gene Expressimentioning
confidence: 99%